Analisis Efektivitas Aplikasi SIHALAL dalam Mempercepat Proses Sertifikasi Halal bagi UMKM di Kabupaten Kapuas - Bidin; Agus Rifai; Beni Andriano (AL-IBNOR, 2026)
This study aims to analyze the effectiveness of the SIHALAL application developed by the Halal Product Guarantee Agency (BPJPH) in accelerating the halal certification process for Micro, Small, and Medium Enterprises (MSMEs) in Kapuas Regency, Central Kalimantan. The method used is descriptive qualitative with a case study approach to understand the extent to which the implementation of the SIHALAL application can improve service efficiency, process transparency, and ease of access for business actors. The results of the study show that the implementation of SIHALAL has contributed significantly to accelerating the halal certification process, with the number of certified MSMEs increasing from 220 units in 2022 to 512 units in 2024. This application has also been able to reduce the time required to apply for certification from 3-6 months to one to two months. However, the effectiveness of SIHALAL is still hampered by low digital literacy, limited internet access in rural areas, and a lack of technical assistance for MSME players. This study emphasizes that optimizing SIHALAL requires support from local governments, halal assistance institutions, and capacity building for business actors so that the halal certification digitization system can run more effectively and sustainably in supporting the strengthening of the sharia economic ecosystem in the region.